SIMANTUL: Model of Internal Quality Audit Management System in Higher Education - Sri Hasta Mulyani; Ariyanto Nugroho; Maisarah Nurain (University of Respati Yogyakarta, Indonesia, 2022)
Many organizations carry out the quality assurance system through the Internal Quality Assurance System (SPMI) and the External Quality Assurance System (SPME). The SPMI framework uses the stages of a continuous quality assurance cycle with the PPEPP method (Application, Implementation, Evaluation, Control, and Improvement), which is carried out periodically to achieve University's Vision, Mission, Goals, and Targets. This paper discusses the implementation stages of the internal quality audit management system at Universitas Respati Yogyakarta, Indonesia. Using an information system, the university audit body, BPM, regularly and consistently carries out an Internal Quality Audit (AMI) every year to audit the implementation of academic and non-academic activities at the University. In this research, we construct an audit system, namely the E-Audit application, with the Waterfall software development method. This study can produce an efficient system called SIMANTUL, which refers to the Higher Education Accreditation assessment instrument version 3.0 and can store documents digitally.